Association between low level of vitamin B12 and cognitive impairment in older adults from the Naval Medical Center of Peru: Asociación entre el bajo nivel de vitamina B12 y deterioro cognitivo en adultos mayores del Centro Médico Naval del Perú - Cabrera Gamonal, Andrés (2023)
Introduction: Older adults are susceptible to malnutrition and vitamin deficiency. Objective: To determine the association between the low level of vitamin B12 and cognitive deterioration in older adults from the Naval Medical Center, located in Lima-Peru, in the period 2010-2015. Methods: An analytical cross-sectional study was carried out, based on a secondary analysis of the Texas-Cemena UTMB 2010-2015 database of the Center for Research on Aging (CIEN) of the University of San Martín de Porres. To quantify the cognitive impairment variable, the MiniMental Test was used. To analyze the association, the Chi-square test and Poisson regression were performed. Results: 57.6% of the patients were male and the mean age was 78 ± 8.4. 41.2% presented cognitive deterioration and 9.5% of the patients presented vitamin B12 deficiency. The factors independently associated with cognitive impairment were a history of cerebrovascular disease (PR= 1.38 95% CI [1.24-1.53]), depression (PR= 1.88 95% CI [1.80-1 .97]) and vitamin B12 deficiency (PR = 1.10 95% CI [1.01-1.20]). Conclusions: In the present study, an association was found between a low level of vitamin B12 and cognitive deterioration in older adults.